2016
DOI: 10.1080/19382014.2016.1235677
|View full text |Cite
|
Sign up to set email alerts
|

Senp2 expression was induced by chronic glucose stimulation in INS1 cells, and it was required for the associated induction of Ccnd1 and Mafa

Abstract: Post-translational modification by bonding of small ubiquitin-like modifier (SUMO) peptides influences various cellular functions, and is regulated by SUMO-specific proteases (SENPs). Several proteins have been suggested to have diverse impact on insulin synthesis and secretion through SUMO modification in β cells. However, the role of SUMO modification in β cell mass has not been established. Here, we examined the changes in expression of Senp in INS1 cells and pancreatic islets under diabetes-relevant stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Our study indicated that senp2 and senp3 mRNA levels were lower for yellow catfish fed the glucose than those fed the dextrin. In contrast, Jung et al (40) found that the expression of Senp2, but not Senp1, was triggered by chronic high-glucose stimulation in insulin-producing cells. Moreover, Jung et al (40) pointed out that the induction of different SENP needed different stimulations according to cell types.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Our study indicated that senp2 and senp3 mRNA levels were lower for yellow catfish fed the glucose than those fed the dextrin. In contrast, Jung et al (40) found that the expression of Senp2, but not Senp1, was triggered by chronic high-glucose stimulation in insulin-producing cells. Moreover, Jung et al (40) pointed out that the induction of different SENP needed different stimulations according to cell types.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, Jung et al (40) found that the expression of Senp2, but not Senp1, was triggered by chronic high-glucose stimulation in insulin-producing cells. Moreover, Jung et al (40) pointed out that the induction of different SENP needed different stimulations according to cell types. In response to glucose, the expression of SENP2 was predominant in the cytoplasm than in the nucleus (40) .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In mammals, several studies indicated that SUMOylation modification of proteins were influenced by carbohydrate (or glucose) levels ( Huang et al, 2013 ; Jung et al, 2016 ), but no such studies were conducted in fish. For the first time, our study explored the effects of dietary carbohydrate levels on mRNA expressions of the 10 genes in four tissues in fish, and detected the effect of glucose incubation on mRNA expressions of SUMOylation related genes in primary hepatocytes from yellow catfish.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Huang et al (2013) reported that high glucose increased the expression of sumo1 and sumo2/3 in glomerular mesangial cells of the rats. Jung et al (2016) pointed out that different stimulations were required for inducing different SENPs according to cell types, and concluded that chronic high glucose was responsible for inducing Senp2 expression in insulin-producing cells.…”
Section: Discussionmentioning
confidence: 99%